Identification of Indonesian Endemic Orchidaceae using Sequence Alignment and Genetic Distance (Biosaintifika: Journal of Biology & Biology Education, 2026)
Orchid is an ornamental plant commodity with a high contribution to horticultural production in Indonesia. Efforts to fulfill market demand have caused the hybridization of many orchids to improve quality and create uniqueness in orchid horticulture. Hybridization is influenced by the genetic distance between orchid species to be crossing over. This study aimed to analyze the genetic relationship of the Indonesian endemic Orchidaceae family using sequence alignment and genetic distance. This descriptive exploratory research uses the bioinformatics method with the genetic distance as a variable. The procedure in this study begins with collecting sequence data in FASTA format, aligning sample sequence data, constructing phylogenetic trees, computing amino acid composition, computing Pairwise Distance, and ends with data analysis. The sample was 16 species of orchids that were selected using a purposive sampling technique with complete sequence data in GenBank. The genetic relationships of the 16 species consist of two major clades. Each clade has a pair of species connected by a straight vertical line indicating genetic distance